Hydrophobic anticorrosive coating and preparation method thereof

By combining kaolin with acrylic resin and adding modified nano silica, a coating with better hydrophobic and anti-corrosion effect is prepared, which solves the problem of the hydrophobic and anti-corrosion coating in the prior art that accelerates metal corrosion and insufficient anti-corrosion performance, and achieves a more efficient anti-corrosion effect.

CN119708939AActive Publication Date: 2025-03-28CHINA TEST & CERTIFICATION INT GRP CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510076644.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-03-28
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The existing hydrophobic anticorrosion coatings may accelerate metal corrosion during work, and their anticorrosion performance needs to be further improved.

Method used

The film is prepared by selecting kaolin and acrylic resin, and the pores are filled by adding modified nanosilicon dioxide to form a coating with better hydrophobic and anti-corrosion effect.

Benefits of technology

It improves the hydrophobicity and corrosion resistance of the coating, effectively blocks corrosive media, and extends the service life of the metal substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708939A_ABST
    Figure CN119708939A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrophobic anticorrosive coating and a preparation method thereof, and belongs to the technical field of anticorrosive coating preparation. The method comprises the following steps: step 1, preparing nano silicon dioxide; step 2, adding kaolin powder, acrylic resin and nano silicon dioxide into ethyl acetate, performing ultrasonic dispersion, and then performing magnetic stirring at room temperature to obtain a pre-cured mixed solution; the mass ratio of the kaolin powder to the acrylic resin to the nano silicon dioxide is 1: 0.66: 0.05; and 3, dispensing the pre-cured mixed solution on a substrate, and curing to obtain the hydrophobic anticorrosive coating. The kaolin and the acrylic resin are selected to prepare the film, the kaolin with the specific particle size can reduce pores of the film as much as possible, and then the pores are further filled with the added modified nano silicon dioxide, so that the prepared coating has better hydrophobic and anti-corrosion effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-corrosion coating preparation, and in particular to a hydrophobic anti-corrosion coating and a preparation method thereof. Background Art

[0002] The adverse effects of metal corrosion on ecology and economy have promoted the research on the development of anti-corrosion coatings, and engineered super-hydrophobic nanostructured coatings are a promising self-cleaning and anti-corrosion application technology. The working principle of hydrophobic anti-corrosion coatings is to isolate the metal substrate from liquid corrosive media such as water and extend the propagation path of liquid corrosive media. However, super-hydrophilic surfaces in the air are generally super-aerophilic; on the contrary, super-hydrophobic surfaces in the air are super-aerophilic. Therefore, hydrophobic anti-corrosion coatings will have higher aerophilic properties than ordinary coatings during operation, making it easier for another corrosive medium O2 to contact the metal substrate, which may also accelerate the corrosion process. Therefore, it is very necessary to explore the scientific issue of the relationship between the hydrophobicity of the coating surface and its corrosion resistance.

[0003] Commonly used anticorrosion coatings mainly include epoxy resin coatings, polyurethane resin coatings, acrylic resin coatings, etc. Among them, acrylic resin anticorrosion coatings have good weather resistance, light and color retention, high gloss and decorativeness, as well as good temperature resistance (resistant to 160°C), fast drying speed, normal curing at 0°C, one-time film thickness, and few construction passes. There are also related patents in the prior art to prepare super-hydrophobic acrylic resins. For example, CN102417773A discloses a super-hydrophobic acrylic resin coating, which is composed of nanoparticles, acrylic resin, mixed solvent, and heptafluorotrimethoxyethoxysilane. The prepared coating surface water droplet contact angle is between 150-160°. CN111269628A discloses a super-hydrophobic anti-fouling flashover coating that can be constructed with electricity and a preparation method thereof. The raw materials of the coating are: modified nano-silica, modified low surface energy resin, dispersant, defoamer, leveling agent, and charged solvent; the modified nano-silica is made of the following raw materials in parts by weight: trifluoropropylmethylcyclotrisiloxane, 1H, 1H, 2H, 2H-perfluorooctyltrichlorosilane, 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane, trifluoromethyltrimethylsilane, nano-silica powder, and charged solvent. The coating formed by the coating prepared by the invention has super-hydrophobic, super-self-cleaning, and anti-fouling capabilities. However, neither of the above two patents discloses whether it has anti-corrosion properties.

[0004] CN118995011A discloses a high temperature resistant super hydrophobic long-acting anticorrosion coating and its preparation method, using γ-methacryloxypropyl trimethoxysilane to surface modify nanoparticles to obtain modified nanoparticles; using vinyl trimethoxysilane to surface modify nano silicon dioxide to obtain super hydrophobic silicon dioxide; modified nanoparticles, super hydrophobic silicon dioxide and methacrylic acid are polymerized, and then grafted onto phenolic epoxy resin by ring-opening reaction to obtain modified epoxy vinyl resin; modified epoxy vinyl resin and curing agent are mixed uniformly, sprayed onto the surface of metal substrate, and high temperature resistant super hydrophobic long-acting anticorrosion coating is obtained after curing. The invention not only improves the crosslinking degree, heat resistance, shielding property and toughness of epoxy vinyl resin, but also improves the hydrophobicity of coating, so that coating has long-acting anticorrosion property. However, the film-forming substance of its anticorrosive coating is epoxy resin, and acrylic resin is not disclosed as its anticorrosion property of film-forming substance.

[0005] CN116410638A uses dodecafluoroheptylpropyltrimethoxysilane as a catalyst, and the silanol produced by the hydrolysis of methacryloxypropyltrimethoxysilane undergoes a condensation reaction with the hydroxyl groups on the surface of nano-scale silica, and then further undergoes a fluorination reaction with perfluorooctylethyltrichlorosilane, introducing a large number of hydrophobic fluorinated groups and alkyl long chains on the surface of nano-silica to prepare a modified silica filler; then the modified fluorinated silica filler and talc powder of different mesh sizes are added to acrylic resin to prepare a compression-resistant and wear-resistant hydrophobic anticorrosive coating. However, its anticorrosion performance needs to be further improved. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides a hydrophobic anti-corrosion coating and a preparation method thereof; the present invention selects kaolin and acrylic resin to prepare a film, kaolin with a specific particle size can reduce the porosity of the film as much as possible, and then the pores are further filled by adding modified nano-silica, so that the prepared coating has a better anti-corrosion effect.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] In one aspect, the present invention provides a method for preparing a hydrophobic anticorrosive coating, comprising:

[0009] Step 1: Preparation of nano-silicon dioxide;

[0010] Step 2: adding kaolin powder, acrylic resin and nano-silica to ethyl acetate, performing ultrasonic dispersion and magnetic stirring at room temperature to obtain a pre-cured mixed solution; the mass ratio of kaolin powder, acrylic resin and nano-silica is 1:0.66:0.05;

[0011] Step 3: Apply the pre-cured mixed liquid dropwise on the substrate and cure it to obtain a hydrophobic anti-corrosion coating.

[0012] Furthermore, in step 2, the particle size of the kaolin powder is 1-10 μm. Preferably, the kaolin powder is a mixture of particle sizes of 1-4 μm and 5-8 μm in a mass ratio of 1:2.5.

[0013] Preferably, the molecular weight of the acrylic resin is 10000-50000. The mass ratio of the volume of ethyl acetate to the acrylic resin is 5 mL: 1 g.

[0014] Furthermore, in step 2, ultrasonic dispersion is performed for 30-60 minutes and magnetic stirring is performed for 1-4 hours.

[0015] In step 2, the substrate is a Q235 steel electrode sheet or a glass sheet; the amount of the pre-cured mixed solution applied is 0.5-2 mL / cm 2 The curing time is 12-24 hours at room temperature.

[0016] Preferably, the preparation method of the nano-silica is as follows: an anhydrous ethanol solution and ammonia water in a volume ratio of 1:1 are dispersed in a beaker; the solution is placed in a magnetic stirring for 0.5 h; then 2 ml of tetraethoxysilane (TEOS) is added dropwise into the continuously stirred mixed solution for 4 h; then the mixture is stirred at 5000 r min -1 Centrifuge for 30 minutes, remove the supernatant, filter the solid, and wash it with ethanol 2-5 times to obtain silica nanoparticles.

[0017] Alternatively, preferably, the preparation method of the nano silicon dioxide is as follows:

[0018] ① Mixing anhydrous ethanol solution and aqueous ammonia, and then stirring the mixed solution to mix evenly to obtain a mixed solution;

[0019] The volume ratio of the ethanol solution to the ammonia water is 1:1; the volume fraction of ethanol in the ethanol solution is 90%, and the mass fraction of NH3·H2O in the ammonia water is 25% to 28%;

[0020] ② Add the silane modifier to the above mixed solution and stir evenly;

[0021] The silane modifier is dimethyldiethoxysilane, vinyltrimethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 1:1.5:2; the volume ratio of the mass of the silane modifier to the mixed solution in ① is: 0.5-0.8g:100mL;

[0022] ③ Under stirring conditions, add tetraethoxysilane dropwise into the mixed solution in ②, and continue stirring for 2-6 hours; the volume ratio of the tetraethoxysilane to the mixed solution in ① is 1:50-100;

[0023] ④ Then add the fluorine-containing modifier and stir evenly; the fluorine-containing modifier is hexafluorobutyl methacrylate and 1H,1H,2H,2H-perfluorodecyltriethoxysilane in a mass ratio of 1:0.8; the mass ratio of the fluorine-containing modifier to the silane modifier is 1:0.4-0.6;

[0024] ⑤ Then centrifuge to obtain a solid product, wash the solid product with anhydrous ethanol for 2 to 5 times, then dry it, grind it and sieve it to obtain nano silicon dioxide.

[0025] On the other hand, the present invention also provides a hydrophobic anti-corrosion coating prepared by the above method.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The present invention uses kaolin and acrylic resin to prepare a film. Kaolin with a specific particle size can reduce the pores of the film as much as possible, and then the pores are further filled by adding modified nano-silicon dioxide, so that the prepared coating has a better hydrophobic anti-corrosion effect. After the nano-silicon dioxide mirror cabinet is modified in the present invention, it can cooperate with kaolin and be well dispersed in acrylic resin with a specific molecular weight. The synergistic effect of the three can effectively fill the gaps on the surface of the coating, thereby blocking more corrosive media outside the surface of the coating. These characteristics improve the barrier and anti-corrosion properties of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 (a) is an IR graph of purchased nano-silicon dioxide nanoparticles, and (b) is an IR graph of nano-silicon dioxide prepared in Example 1 of the present invention;

[0029] Figure 2 (a)-(b) are SEM images of nano-silicon dioxide prepared in Example 1 of the present invention, and (c)-(d) are TEM images of nano-silicon dioxide prepared in Example 1 of the present invention;

[0030] Figure 3 SEM images of the coatings prepared in (a) Comparative Example 1, (b) Example 1, (c) Comparative Example 2, (d) Comparative Example 3, (e) Comparative Example 4, (f) Comparative Example 5, and (g) Comparative Example 6, wherein the inset is a picture of the contact angle of the coating to water;

[0031] Figure 4(a) is the impedance result of the hydrophobic coating of Comparative Example 1, Example 1, Comparative Example 2, and Comparative Example 3 when immersed in a 3.5wt% NaCl solution for 1 day, (b) is the impedance result of the hydrophobic coating of Comparative Example 1, Example 1, Comparative Example 2, and Comparative Example 3 when immersed in a 3.5wt% NaCl solution for 3 days, (c) is the impedance result of the hydrophobic coating of Comparative Example 1, Example 1, Comparative Example 2, and Comparative Example 3 when immersed in a 3.5wt% NaCl solution for 7 days;

[0032] Figure 5 (a) is the impedance result of the hydrophobic coating of Comparative Example 4, Comparative Example 5 and Comparative Example 6 when immersed in 3.5wt% NaCl solution for 1 day, (b) is the impedance result of the hydrophobic coating of Comparative Example 4, Comparative Example 5 and Comparative Example 6 when immersed in 3.5wt% NaCl solution for 3 days, (c) is the impedance result of the hydrophobic coating of Comparative Example 4, Comparative Example 5 and Comparative Example 6 when immersed in 3.5wt% NaCl solution for 7 days;

[0033] Figure 6 (a) is the Bode result of the hydrophobic coating of Comparative Example 1, Example 1, Comparative Example 2, and Comparative Example 3 when immersed in a 3.5wt% NaCl solution for 1 day, (b) is the Bode result of the hydrophobic coating of Comparative Example 1, Example 1, Comparative Example 2, and Comparative Example 3 when immersed in a 3.5wt% NaCl solution for 3 days, (c) is the Bode result of the hydrophobic coating of Comparative Example 1, Example 1, Comparative Example 2, and Comparative Example 3 when immersed in a 3.5wt% NaCl solution for 7 days;

[0034] Figure 7 (a) is the Bode result of the hydrophobic coating of Comparative Example 4, Comparative Example 5 and Comparative Example 6 when immersed in 3.5wt% NaCl solution for 1 day, (b) is the Bode result of the hydrophobic coating of Comparative Example 4, Comparative Example 5 and Comparative Example 6 when immersed in 3.5wt% NaCl solution for 3 days, (c) is the Bode result of the hydrophobic coating of Comparative Example 4, Comparative Example 5 and Comparative Example 6 when immersed in 3.5wt% NaCl solution for 7 days. DETAILED DESCRIPTION

[0035] In order to make the technical problems to be solved, technical solutions and advantages of the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0036] In the present invention, the materials and reagents used can be obtained from commercial sources unless otherwise specified. The volume fraction of ethanol in the ethanol solution is 90%, and the mass fraction of NH3·H2O in the ammonia water is 28%.

[0037] The present invention provides a hydrophobic anti-corrosion coating and a preparation method thereof, and specific embodiments are as follows.

[0038] Example 1

[0039] A method for preparing a hydrophobic anticorrosive coating, comprising:

[0040] Step 1: Preparation of nano-silica:

[0041] Disperse anhydrous ethanol (50 ml) and ammonia solution (50 ml) in a 250 mL beaker. Place the mixed solution under magnetic stirring for 0.5 h until the solution no longer stratifies. Add 2 ml of tetraethoxysilane (TEOS) dropwise into the mixed solution under continuous stirring. Floccules appear in the solution. Continue stirring for 4 h until silica spheres are no longer produced. -1 The mixture was centrifuged in a high-speed centrifuge (30 min), the supernatant was removed, the solid was filtered (the filter membrane was a PVC membrane with a pore size of 0.22 μm), the residual anhydrous ethanol and ammonia water were removed, and the mixture was washed twice with ethanol to obtain homemade silica nanoparticles;

[0042] Step 2: 1.0 g of kaolin powder, 0.66 g of acrylic resin AR (SGR-7120 (molecular weight 13000) of Guangzhou Changhao Trading Co., Ltd. (formerly Guangzhou Xianghao Chemical Co., Ltd.)), and 0.05 g of nano-silica were added to ethyl acetate, ultrasonically dispersed for 30 min, then magnetically stirred for 4 h, and then magnetically stirred at room temperature to obtain a pre-cured mixed solution; the kaolin powder was a mixture of particle sizes of 1-4 μm and 5-8 μm in a mass ratio of 1:2.5;

[0043] Step 3: Apply the pre-cured mixed solution to the Q235 steel electrode sheet at a drop size of 2 mL / cm 2 , cured at room temperature for 24 hours to obtain a hydrophobic anticorrosive coating, denoted as CK 1.0 SO 0.05 AR (x represents kaolin content, y represents modified silica content).

[0044] In order to further illustrate the beneficial effects of the present invention, the following comparative example was constructed.

[0045] Comparative Example 1

[0046] In this comparative example, the amount of nano-silicon dioxide used was 0 g, and the other conditions were the same as in Example 1. The obtained coating was recorded as CK 1.0 SO0AR.

[0047] Comparative Example 2

[0048] In this comparative example, 0.10 g of nano-silicon dioxide was used, and the other conditions were the same as those in Example 1. The obtained coating was recorded as CK 1.0 SO 0.10 AR.

[0049] Comparative Example 3

[0050] In this comparative example, the amount of kaolin powder used was 0.17 g, and the other conditions were the same as in Example 1. The obtained coating was recorded as CK 1.0 SO 0.17 AR.

[0051] Comparative Example 4

[0052] In this comparative example, the amount of kaolin powder used was 0.20 g, and the other conditions were the same as in Example 1. The obtained coating was recorded as CK 1.0 SO 0.20 AR.

[0053] Comparative Example 5

[0054] In this comparative example, the amount of kaolin powder used was 0.25 g, and the other conditions were the same as in Example 1. The obtained coating was recorded as CK 1.0 SO 0.25 AR.

[0055] Comparative Example 6

[0056] In this comparative example, the amount of kaolin powder used was 0.30 g, and the other conditions were the same as in Example 1. The obtained coating was recorded as CK 1.0 SO 0.30 AR.

[0057] The coatings obtained in the above examples and comparative examples were subjected to performance tests, and the results are as follows.

[0058] In order to observe the difference between homemade silica nanoparticles and purchased silica nanoparticles, and whether the homemade silica nanoparticles were successfully added to the coating, infrared testing was used to characterize the particles and the superhydrophobic coating. Figure 1 (a) and (b) are infrared scanning spectra of purchased nano-silicon dioxide nanoparticles and homemade nano-silicon dioxide nanoparticles, respectively. It can be clearly observed from the figure that the homemade nano-silicon dioxide nanoparticles have a wavelength of 468 cm -1 and 800cm -1 The Si-O bond vibration peak at and the Si-O-Si bond vibration peak at 1101cm-1 are smaller than those of the purchased nano-silica nanoparticles, but a Si-OH bond vibration peak appears at 943cm-1 that is not present in the purchased nano-silica nanoparticles. This proves that the number of hydroxyl groups on the periphery of the homemade silica particles is significantly increased, making it easier to undergo substitution reactions and be modified into hydrophobic particles.

[0059] TEOS molecules are hydrolyzed under the catalysis of ammonium hydroxide, converting TEOS groups to form Si-OH groups, and condensation reactions occur between adjacent Si-OH groups, thereby inducing the self-assembly of Si-OH-covered nano-silica particles. Figure 2Scanning electron microscope and transmission electron microscope for the generation of nano-silicon dioxide particle spheres. Through the observation of the morphology of the silica particle size, it was found that the generated nano-silicon dioxide particles were evenly distributed, with a particle size of about 450±50nm, and an average nano-silicon dioxide particle size of 470nm.

[0060] In order to study the surface characteristics of different hydrophobic coatings and the wettability of hydrophobic coatings, the coatings were characterized by scanning electron microscopy and hydrophobic angle test. Figure 3 The amounts of modified nano-silica in (a), (b), (c), (d), (e), (f) and (g) are 0g, 0.05g, 0.10g, 0.17g, 0.20g, 0.25g and 0.30g respectively. Figure 3 It can be seen that (a), (b), (c), (d), (e), (f) and (g) show SEM images with hydrophobic angles of 125°, 130°, 135°, 140°, 145°, 150° and 156°, respectively. Figure 3 From (a) and (b), when the hydrophobic angle increases from 125° to 135°, as the number of coating particles increases, the particles will block the pores in the coating, and it is speculated that the coating's ability to block water molecules and oxygen molecules in the air will also increase. Figure 3 From (c) and (d), when the contact angle of the coating is greater than 135°, the coating gradually accumulates with the gradual increase of particles, forming a stacking structure, which increases the probability of contact between the substrate and water molecules and oxygen molecules in the air. When the contact angle reaches 140°, the stacking structure forms the most macropores, and the probability of contact between the substrate and water molecules and oxygen molecules in the air is the greatest, and the corrosion resistance of the coating should be the worst. Figure 3 (e), (f), and (g) show that when the contact angle increases from 145° to 156°, as the hydrophobic angle of the coating increases, the number of pores formed by the stacking structure is almost the same, and the size of the pores shows a slightly decreasing trend. It is inferred that the corrosion resistance of the coating is almost the same, showing a slightly increasing trend. In order to verify this result, an electrochemical workstation is used to represent the corrosion resistance of each coating, thereby indicating the changing trend of the probability of the substrate contacting water molecules and oxygen molecules in the air.

[0061] In order to determine the anti-corrosion ability of different hydrophobic coatings, electrochemical tests were carried out on Q235 steel electrode sheets coated with different hydrophobic coatings. The impedance test results are shown in Figure 2. Figure 4-5 shown.

[0062] Figure 4(a) is the impedance result of the hydrophobic coating of Comparative Example 1, Example 1, Comparative Example 2, and Comparative Example 3 when immersed in 3.5wt% NaCl solution for 1 day, (b) is the impedance result of the hydrophobic coating of Comparative Example 1, Example 1, Comparative Example 2, and Comparative Example 3 when immersed in 3.5wt% NaCl solution for 3 days, (c) is the impedance result of the hydrophobic coating of Comparative Example 1, Example 1, Comparative Example 2, and Comparative Example 3 when immersed in 3.5wt% NaCl solution for 7 days. The specific data are shown in Table 1.

[0063] Table 1

[0064]

[0065] Comparative Example 1, Example 1, Comparative Example 2, Comparative Example 3 The hydrophobic coating has a hydrophobic angle of 125°-140°. As shown in Table 1, when immersed in 3.5wt% NaCl solution for 1 day, CK 1.0 SO 0.05 The AR coating has a maximum impedance ring radius of about 3.80×10 6 Ω·cm 2 , which is almost one to two orders of magnitude larger than the impedance radius of other hydrophobic coatings, CK 1.0 The impedance radius of the SO0AR coating is 3.30×10 5 Ω·cm 2 With CK 1.0 SO 0.10 The impedance radius of AR coating is 2.88×10 5 Ω·cm 2 Almost the same, both in CK 1.0 SO 0.17 The impedance radius of AR coating is 2.36×10 4 Ω·cm 2 This means that for coatings with a hydrophobic angle of 125°-140°, after being immersed in a 3.5wt% NaCl solution for 1 day, the corrosion resistance first increases and then decreases, and the corrosion resistance of the coating with a hydrophobic angle of 130° is the best. After being immersed in a 3.5wt% NaCl solution for 3 days, CK 1.0 SO 0.05 The AR coating has a maximum impedance ring radius of 2.86×10 6 Ω·cm 2 , C.K. 1.0 The impedance radius of the SO0AR coating is 2.41×10 5 Ω·cm 2 , greater than CK 1.0 SO 0.10 The impedance radius of AR coating is 1.98×10 5 Ω·cm 2, both greater than CK 1.0 SO 0.17 The impedance radius of AR coating is 1.63×10 4 Ω·cm 2 It is proved that for the coating with a hydrophobic angle of 125°-140°, the anti-corrosion ability after immersion in 3.5wt% NaCl solution for 3 days is consistent with that after immersion in NaCl solution for 1 day. After immersion in 3.5wt% NaCl solution for 7 days, CK 1.0 SO 0.05 The impedance radius of the AR coating is 1.42×10 6 Ω·cm 2 , one to two orders of magnitude higher than other coatings. 1.0 The impedance radius of the SO0AR coating is 1.76×10 5 Ω·cm 2 , greater than CK 1.0 SO 0.10 The impedance radius of AR coating is 1.51×10 5 Ω·cm 2 , both higher than CK 1.0 SO 0.17 The impedance radius of AR coating is 1.17×10 4 Ω·cm 2 It is proved that for the coating with a hydrophobic angle of 125°-140°, when immersed in 3.5wt% NaCl solution for 7 days, the anti-corrosion ability is consistent with that when immersed in NaCl solution for 1 day and 3 days.

[0066] Figure 5 (a) is the impedance result of the hydrophobic coating of (e) Comparative Example 4, (f) Comparative Example 5 and (g) Comparative Example 6 when immersed in 3.5wt% NaCl solution for 1 day, (b) is the impedance result of the hydrophobic coating of (e) Comparative Example 4, (f) Comparative Example 5 and (g) Comparative Example 6 when immersed in 3.5wt% NaCl solution for 3 days, (c) is the impedance result of the hydrophobic coating of (e) Comparative Example 4, (f) Comparative Example 5 and (g) Comparative Example 6 when immersed in 3.5wt% NaCl solution for 7 days. See Table 2 for specific data.

[0067] Table 2

[0068]

[0069] For coatings with hydrophobic angles of 145°-156°, CK 1.0 SO 0.30 The AR coating has a maximum impedance ring radius of 1.03×10 5 Ω·cm 2 , greater than CK1.0 SO 0.25 The impedance radius of AR coating is 6.54×10 4 Ω·cm 2 , both greater than CK 1.0 SO 0.20 The AR coating has a diameter of 5.81×10 4 Ω·cm 2 This shows that for the coating with a hydrophobic angle of 145°-156°, the anti-corrosion ability shows an upward trend when immersed in 3.5wt% NaCl solution for 1 day, but the anti-corrosion ability is weaker than that of the coating with a hydrophobic angle of 130°. 1.0 SO 0.30 The AR coating has an impedance ring with the largest radius, which is 8.81×10 4 Ω·cm 2 , greater than CK 1.0 SO 0.25 The impedance radius of AR coating is 6.16×10 4 Ω·cm 2 , both greater than CK 1.0 SO 0.20 The AR coating has a diameter of 5.38×10 4 Ω·cm 2 , which is consistent with the corrosion law of immersion for 1 day. When immersed in 3.5wt% NaCl solution for 7 days, CK 1.0 SO 0.30 The AR coating has a maximum impedance ring radius of 7.57×10 4 Ω·cm 2 , greater than CK 1.0 SO 0.25 The impedance radius of AR coating is 4.89×10 4 Ω·cm 2 , both greater than CK 1.0 SO 0.20 The AR coating has a diameter of 2.55×10 4 Ω·cm 2 , which is consistent with the rule of soaking for 1 day and 3 days.

[0070] For the Bode test of different hydrophobic coatings, the results are as follows Figure 6 , Figure 7 shown. Figure 6(a) is the Bode result of the hydrophobic coating of Comparative Example 1, Example 1, Comparative Example 2, and Comparative Example 3 when immersed in 3.5wt% NaCl solution for 1 day, (b) is the Bode result of the hydrophobic coating of Comparative Example 1, Example 1, Comparative Example 2, and Comparative Example 3 when immersed in 3.5wt% NaCl solution for 3 days, (c) is the Bode result of the hydrophobic coating of Comparative Example 1, Example 1, Comparative Example 2, and Comparative Example 3 when immersed in 3.5wt% NaCl solution for 7 days.

[0071] For coatings with hydrophobic angles of 125°-140°, CK 1.0 SO 0.05 The AR coating has the largest Bode modulus at f = 0.1 Hz, which is about 3.75×10 6 Ω·cm 2 , which is one to two orders of magnitude larger than other hydrophobic coatings, CK 1.0 The modulus of SO0AR coating is 3.20×10 5 Ω·cm 2 Greater than CK 1.0 SO 0.10 The modulus of AR coating is 2.70×10 5 Ω·cm 2, , both greater than CK 1.0 SO 0.10 The modulus of AR coating is 2.20×10 4 Ω·cm 2 This means that for coatings with a hydrophobic angle of 125°-140°, after being immersed in a 3.5wt% NaCl solution for 1 day, the corrosion resistance first increases and then decreases, and the corrosion resistance of the coating with a hydrophobic angle of 130° is the best, which is consistent with the impedance diagram. 1.0 SO 0.05 The AR coating has a maximum modulus value of 2.70×10 6 Ω·cm 2 , C.K. 1.0 The modulus of SO0AR coating is 2.40×10 5 Ω·cm 2 Greater than CK 1.0 SO 0.10 The modulus of AR coating is 1.85×10 5 Ω·cm 2 Almost the same, both larger than CK 1.0 SO 0.17 The modulus of AR coating is 1.52×10 4 Ω·cm 2, the anti-corrosion law is the same as that of immersion for 1 day. After immersion in 3.5wt% NaCl solution for 7 days, CK 1.0 SO 0.05 The AR coating has a maximum modulus value of 1.40×10 6 Ω·cm 2 , C.K. 1.0 The modulus of SO0AR coating is 1.75×10 5 Ω·cm 2 Greater than CK 1.0 SO 0.10 The modulus of AR coating is 1.45×10 5 Ω·cm 2 Almost the same, both larger than CK 1.0 SO 0.17 The modulus of AR coating is 1.14×10 4 Ω·cm 2 The anti-corrosion law is consistent with that of immersion for 1 day and 3 days, and is consistent with the EIS corrosion law.

[0072] Figure 7 (a) is the Bode result of the hydrophobic coating of Comparative Example 4, Comparative Example 5 and Comparative Example 6 when immersed in a 3.5wt% NaCl solution for 1 day, (b) is the Bode result of the hydrophobic coating of Comparative Example 4, Comparative Example 5 and Comparative Example 6 when immersed in a 3.5wt% NaCl solution for 3 days, (c) is the Bode result of the hydrophobic coating of Comparative Example 4, Comparative Example 5 and Comparative Example 6 when immersed in a 3.5wt% NaCl solution for 7 days;

[0073] For coatings with hydrophobic angles of 145°-156°, CK 1.0 SO 0.30 The AR coating has the largest Bode modulus value at f = 0.1 Hz, which is about 1.30×10 5 Ω·cm 2 , greater than CK 1.0 SO 0.25 The modulus of AR coating is 8.80×10 4 Ω·cm 2 Both greater than CK 1.0 SO 0.20 The modulus value of AR coating is 8.02×104Ω·cm2. This means that for coatings with hydrophobic angles of 145°-156°, the corrosion resistance shows an upward trend after being immersed in 3.5wt% NaCl solution for 1 day, which is consistent with the impedance diagram. 1.0 SO 0.30 The AR coating has the largest Bode modulus value, which is about 1.17×10 5Ω·cm 2 , greater than CK 1.0 SO 0.25 The modulus of AR coating is 7.80×10 4 Ω·cm 2 Both greater than CK 1.0 SO 0.20 The modulus of AR coating is 7.42×10 4 Ω·cm 2 , which is consistent with the corrosion law of immersion for 1 day. After immersion in 3.5wt% NaCl solution for 7 days, CK 1.0 SO 0.30 The AR coating has the largest Bode modulus value, which is about 1.01×10 5 Ω·cm 2 , greater than CK 1.0 SO 0.25 The modulus of AR coating is 6.05×10 4 Ω·cm 2 Both greater than CK 1.0 SO 0.20 The modulus of AR coating is 3.82×10 4 Ω·cm 2 , which is consistent with the corrosion rules of immersion for 1 day, 3 days and impedance.

[0074] In order to further illustrate the beneficial effects of the present invention, the inventors also designed the following comparative examples.

[0075] Comparative Example 7

[0076] In this comparative example, the amount of acrylic resin used is 0.5 g, and the other conditions are the same as in Example 1.

[0077] Comparative Example 8

[0078] In this comparative example, the amount of acrylic resin used is 1 g, and the other conditions are the same as in Example 1.

[0079] Comparative Example 9

[0080] In this comparative example, the amount of kaolin used is 0.5 g, and the other conditions are the same as those in Example 1.

[0081] Comparative Example 10

[0082] In this comparative example, the amount of kaolin used was 1.2 g, and the other conditions were the same as in Example 1.

[0083] Comparative Example 11

[0084] In this comparative example, the particle size of kaolin is 500-800 nm, and the other conditions are the same as those in Example 1.

[0085] Comparative Example 12

[0086] In this comparative example, the particle size of kaolin is 1-4 μm, and the other conditions are the same as those in Example 1.

[0087] Comparative Example 13

[0088] In this comparative example, the particle size of kaolin is 5-8 μm, and the other conditions are the same as those in Example 1.

[0089] Comparative Example 14

[0090] In this comparative example, the kaolin powder is a mixture of 1-4 μm and 5-8 μm in a mass ratio of 1:1, and the other conditions are the same as those in Example 1.

[0091] Comparative Example 15

[0092] In this comparative example, the kaolin powder is a mixture of particle sizes of 1-4 μm and 5-8 μm in a mass ratio of 1:3, and the other conditions are the same as those in Example 1.

[0093] The performance of the coating prepared in the above comparative example was compared with the hydrophobic coating prepared in Example 1. The results are shown in Table 3-4.

[0094] Table 3

[0095]

[0096] As shown in Table 3, adjusting the amount of acrylic resin and kaolin will lead to changes in the contact angle, and adjusting the particle size and proportion of kaolin will also lead to changes in the contact angle.

[0097] Table 4 shows the impedance results of the coatings prepared in Comparative Examples 7-15 when immersed in a 3.5 wt % NaCl solution for 1 day, 3 days and 7 days.

[0098] Table 4

[0099]

[0100] It can be seen from Table 4 that by reducing or increasing the amount of acrylate and kaolin or adjusting the particle size of kaolin, the impedance radius of the prepared anti-corrosion coating is reduced by 2 orders of magnitude; this may be because the increase in the contact angle allows the coating to absorb air with an air layer, and the coating has more pores, which increases the probability of contact between the corrosive medium and the substrate, thereby reducing the corrosion resistance of the coating, and reducing the impedance radius of the prepared anti-corrosion coating by two orders of magnitude.

[0101] The present invention also optimizes the preparation method of nano silicon dioxide, and the specific embodiments are as follows.

[0102] Example 2

[0103] A method for preparing a hydrophobic anticorrosive coating, comprising:

[0104] Step 1: Preparation of nano-silica:

[0105] ① Disperse anhydrous ethanol (50 ml) and ammonia solution (50 ml) in a 250 mL beaker. Place the mixed solution under magnetic stirring for 0.5 h until the solution no longer separates;

[0106] ② Add 0.6 g of silane modifier to the mixed solution and stir evenly; wherein the silane modifier is dimethyldiethoxysilane, vinyltrimethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 1:1.5:2;

[0107] ③ Under stirring conditions, add 2 mL of tetraethoxysilane dropwise into the mixed solution of ② and continue stirring for 4 h;

[0108] ④ Then add 1.0g of fluorine-containing modifier and stir evenly; the fluorine-containing modifier is hexafluorobutyl methacrylate and 1H,1H,2H,2H-perfluorodecyltriethoxysilane in a mass ratio of 1:0.8;

[0109] ⑤Then use 5000r min -1 The mixture was centrifuged in a high-speed centrifuge (30 min), the supernatant was removed, and the solid component was filtered (the filter membrane was a PVC membrane with a pore size of 0.22 μm) to obtain a solid product, which was washed three times with anhydrous ethanol, then dried in an oven at 60 degrees Celsius, and ground through a 5000-mesh sieve to obtain nano-silicon dioxide;

[0110] Step 2: 1.0 g of kaolin powder, 0.66 g of acrylic resin AR (SGR-7120 (molecular weight 13000) of Guangzhou Changhao Trading Co., Ltd. (formerly Guangzhou Xianghao Chemical Co., Ltd.)), and 0.05 g of nano-silica were added to ethyl acetate, ultrasonically dispersed for 30 min, then magnetically stirred for 4 h, and then magnetically stirred at room temperature to obtain a pre-cured mixed solution; the kaolin powder was a mixture of particle sizes of 1-4 μm and 5-8 μm in a mass ratio of 1:2.5;

[0111] Step 3: Apply the pre-cured mixed solution to the Q235 steel electrode sheet at a drop size of 2 mL / cm 2 , cured at room temperature for 24 hours to obtain a hydrophobic anti-corrosion coating.

[0112] Example 3

[0113] In this embodiment, the acrylic resin is Japanese Mitsubishi BR-113 (molecular weight 30000), and the other conditions are the same as in Example 2.

[0114] Example 4

[0115] In this embodiment, the acrylic resin is Japanese Mitsubishi BR-116 (molecular weight 45000), and the other conditions are the same as in Example 2.

[0116] Example 5

[0117] A method for preparing a hydrophobic anticorrosive coating, comprising:

[0118] Step 1: Preparation of modified nano-silica:

[0119] ① Disperse anhydrous ethanol (50 ml) and ammonia solution (50 ml) in a 250 mL beaker. Place the mixed solution under magnetic stirring for 0.5 h until the solution no longer separates;

[0120] ② Add 0.5 g of silane modifier to the mixed solution and stir evenly; wherein the silane modifier is dimethyldiethoxysilane, vinyltrimethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 1:1.5:2;

[0121] ③ Under stirring conditions, add 1 mL of tetraethoxysilane dropwise into the mixed solution in ②, and continue stirring for 2 hours; the volume ratio of the tetraethoxysilane to the mixed solution in ① is 1:50-100;

[0122] ④ Then add 1.0g of fluorine-containing modifier and stir evenly; the fluorine-containing modifier is hexafluorobutyl methacrylate and 1H,1H,2H,2H-perfluorodecyltriethoxysilane in a mass ratio of 1:0.8;

[0123] ⑤Then use 5000r min -1 The mixture was centrifuged in a high-speed centrifuge (30 min), the supernatant was removed, and the solid component was filtered (the filter membrane was a PVC membrane with a pore size of 0.22 μm) to obtain a solid product. The solid product was washed three times with anhydrous ethanol, then dried in an oven at 60 degrees Celsius, and ground through a 5000-mesh sieve to obtain modified nano-silica.

[0124] Step 2: 1.0 g of kaolin powder, 0.66 g of acrylic resin AR (BR-113 (molecular weight 30,000) of Guangzhou Changhao Trading Co., Ltd. (formerly Guangzhou Xianghao Chemical Co., Ltd.)), and 0.05 g of modified nano-silica were added to ethyl acetate, ultrasonically dispersed for 40 min, then magnetically stirred for 2 h, and then magnetically stirred at room temperature to obtain a pre-cured mixed solution; the kaolin powder was a mixture of particle sizes of 1-4 μm and 5-8 μm in a mass ratio of 1:2.5;

[0125] Step 3: Apply the pre-cured mixed solution to the Q235 steel electrode sheet at a drop size of 1 mL / cm 2 , cured at room temperature for 18 hours to obtain a hydrophobic anti-corrosion coating.

[0126] Example 6

[0127] A method for preparing a hydrophobic anticorrosive coating, comprising:

[0128] Step 1: Preparation of modified nano-silica:

[0129] ① Disperse anhydrous ethanol (50 ml) and ammonia solution (50 ml) in a 250 mL beaker. Place the mixed solution under magnetic stirring for 0.5 h until the solution no longer separates;

[0130] ② Add 0.8 g of silane modifier to the mixed solution and stir evenly; wherein the silane modifier is dimethyldiethoxysilane, vinyltrimethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 1:1.5:2;

[0131] ③ Under stirring conditions, add 2 mL of tetraethoxysilane dropwise into the mixed solution in ② and continue stirring for 6 hours; the volume ratio of tetraethoxysilane to the mixed solution in ① is 1:50-100;

[0132] ④ Then add 1.6g of fluorine-containing modifier and stir evenly; the fluorine-containing modifier is hexafluorobutyl methacrylate and 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane in a mass ratio of 1:0.8;

[0133] ⑤Then use 5000r min -1 The mixture was centrifuged in a high-speed centrifuge (30 min), the supernatant was removed, and the solid component was filtered (the filter membrane was a PVC membrane with a pore size of 0.22 μm) to obtain a solid product. The solid product was washed 5 times with anhydrous ethanol, then dried in an oven at 60 degrees Celsius, and ground through a 5000-mesh sieve to obtain modified nano-silica.

[0134] Step 2: 1.0 g of kaolin powder, 0.66 g of acrylic resin AR (BR-113 (molecular weight 30,000) of Guangzhou Changhao Trading Co., Ltd. (formerly Guangzhou Xianghao Chemical Co., Ltd.), and 0.05 g of modified nano-silica were added to ethyl acetate, ultrasonically dispersed for 60 min, magnetically stirred for 1 h, and then magnetically stirred at room temperature to obtain a pre-cured mixed solution; the kaolin powder was a mixture of particle sizes of 1-4 μm and 5-8 μm in a mass ratio of 1:2.5;

[0135] Step 3: Apply the pre-cured mixed solution to the Q235 steel electrode substrate at a drop size of 0.5 mL / cm 2 , cured at room temperature for 12 hours to obtain a hydrophobic anti-corrosion coating.

[0136] The hydrophobic and anti-corrosion properties of the hydrophobic and anti-corrosion coatings prepared in the above examples were tested, and the results are shown in Tables 5-6.

[0137] Table 5

[0138] Sample No. Contact angle / ° Example 2 156.23 Example 3 153.14 Example 4 151.42 Example 5 148.68 Example 6 144.73

[0139] It can be seen from Table 5 that modifying nano-silica can effectively increase its contact angle with water.

[0140] The impedance results of the coatings prepared in Examples 2-6 when immersed in 3.5 wt % NaCl solution for 1 day, 3 days and 7 days are shown in Table 6.

[0141] Table 6

[0142]

[0143] It can be seen from Table 6 that the anti-corrosion performance of nano-silicon dioxide can be improved on the original basis after modification, and the impedance radius is increased by 1-2 orders of magnitude. This proves that the method of the present invention successfully prepares an anti-corrosion coating with good hydrophobicity and excellent anti-corrosion ability.

[0144] In order to further illustrate the effect of the preparation of nano-silicon dioxide on the coating, the following comparative example was constructed.

[0145] Comparative Example 16

[0146] In this comparative example, the acrylic resin is Japanese Mitsubishi BR-106 (molecular weight 60000), and the other conditions are the same as those in Example 2.

[0147] Comparative Example 17

[0148] In this comparative example, the silane modifier is vinyltrimethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 2.5:2, and the other conditions are the same as those in Example 2.

[0149] Comparative Example 18

[0150] In this comparative example, the silane modifier is dimethyldiethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 2.5:2, and the other conditions are the same as those in Example 2.

[0151] Comparative Example 19

[0152] In this comparative example, the silane modifier is vinyltrimethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 1.5:3, and the other conditions are the same as those in Example 2.

[0153] Comparative Example 20

[0154] In this comparative example, the silane modifier is dimethyldiethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 1:3.5, and the other conditions are the same as those in Example 2.

[0155] Comparative Example 21

[0156] In this comparative example, the silane modifier is dimethyldiethoxysilane, vinyltrimethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 1:1:1, and the other conditions are the same as in Example 2.

[0157] Comparative Example 22

[0158] In this comparative example, the silane modifier is dimethyldiethoxysilane, vinyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane in a mass ratio of 1:1:1, and the other conditions are the same as in Example 2.

[0159] Comparative Example 23

[0160] In this comparative example, the fluorine-containing modifier is hexafluorobutyl methacrylate, and the other conditions are the same as those in Example 2.

[0161] Comparative Example 24

[0162] In this comparative example, the fluorine-containing modifier is 1H,1H,2H,2H-perfluorodecyltriethoxysilane, and the other conditions are the same as those in Example 2.

[0163] Comparative Example 25

[0164] In this comparative example, the fluorine-containing modifier is hexafluorobutyl methacrylate and 1H,1H,2H,2H-perfluorodecyltriethoxysilane in a mass ratio of 1:1, and the other conditions are the same as those in Example 2.

[0165] Comparative Example 26

[0166] In this comparative example, the fluorine-containing modifier is hexafluorobutyl methacrylate and 1H,1H,2H,2H-perfluorodecyltriethoxysilane in a mass ratio of 0.8:1, and the other conditions are the same as those in Example 2.

[0167] Comparative Example 27

[0168] In this comparative example, the fluorine-containing modifier is hexafluorobutyl methacrylate and 1H,1H,2H,2H-perfluorodecyltriethoxysilane in a mass ratio of 1:0.5, and the other conditions are the same as those in Example 2.

[0169] Comparative Example 28

[0170] In this comparative example, the fluorine-containing modifier is dodecafluoroheptyl methacrylate and 1H,1H,2H,2H-perfluorodecyltriethoxysilane in a mass ratio of 1:0.8, and the other conditions are the same as those in Example 2.

[0171] Comparative Example 29

[0172] A method for preparing a hydrophobic anticorrosive coating, comprising:

[0173] Step 1: Preparation and modification of nano-silica

[0174] Disperse anhydrous ethanol (50 ml) and ammonia solution (50 ml) in a 250 mL beaker. Place the mixed solution under magnetic stirring for 0.5 h until the solution no longer stratifies. Add 2 ml of tetraethoxysilane (TEOS) dropwise into the mixed solution under continuous stirring. Floccules appear in the solution. Continue stirring for 4 h until silica spheres are no longer produced. -1 The mixture was centrifuged in a high-speed centrifuge (30 min), the supernatant was removed, the solid was filtered (the filter membrane was a PVC membrane with a pore size of 0.22 μm), the residual anhydrous ethanol and ammonia water were removed, and the mixture was washed twice with ethanol to obtain homemade silica nanoparticles;

[0175] Weigh 1g of nano-SiO2 particles, add them to a flask containing 50ml of ethanol and add 1ml of ammonia water, place it in an ultrasonic cleaner for ultrasonic dispersion for 30min, make SiO2 evenly dispersed, and obtain a nano-SiO2 / ethanol suspension. Subsequently, quickly add 2ml of octadecyltrimethoxysilane under stirring and react for 4h. After the modification reaction is completed, the obtained liquid is centrifuged in a centrifuge at a speed of 5000r for 30min to separate it, and then washed twice with ethanol, and the obtained solid is placed in a 60℃ oven and dried for 12h and fully ground to obtain a modified nano-SiO2 powder.

[0176] Steps 2-3 are the same as in Example 2 to obtain an anti-corrosion coating.

[0177] Comparative Example 30

[0178] A method for preparing a hydrophobic anticorrosive coating, comprising:

[0179] Step 1: Preparation and modification of nano-silica

[0180] Disperse anhydrous ethanol (50 ml) and ammonia solution (50 ml) in a 250 mL beaker. Place the mixed solution under magnetic stirring for 0.5 h until the solution no longer stratifies. Add 2 ml of tetraethoxysilane (TEOS) dropwise into the mixed solution under continuous stirring. Floccules appear in the solution. Continue stirring for 4 h until silica spheres are no longer produced. -1 The mixture was centrifuged in a high-speed centrifuge (30 min), the supernatant was removed, the solid was filtered (the filter membrane was a PVC membrane with a pore size of 0.22 μm), the residual anhydrous ethanol and ammonia water were removed, and the mixture was washed twice with ethanol to obtain homemade silica nanoparticles;

[0181] Weigh 1g of nano-SiO2 particles, add it to a flask containing 50ml of ethanol and add 1ml of ammonia water, place it in an ultrasonic cleaner for ultrasonic dispersion for 30min, so that SiO2 is evenly dispersed to obtain a nano-SiO2 / ethanol suspension. Subsequently, 2ml of dimethyldiethoxysilane, vinyltrimethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 1:1.5:2 are quickly added under stirring conditions, and then reacted for 4h. After the modification reaction is completed, the obtained liquid is centrifuged in a centrifuge at a speed of 5000r for 30min to separate it, and then washed twice with ethanol, and the obtained solid is placed in a 60℃ oven to dry for 12h and fully ground to obtain a modified nano-SiO2 powder.

[0182] Steps 2-3 are the same as in Example 2 to obtain an anti-corrosion coating.

[0183] The performance of the coating prepared in the above comparative example was compared with the hydrophobic coating prepared in Example 2. The results are shown in Tables 7-10.

[0184] Table 7

[0185]

[0186] It can be seen from Table 7 that regulating the molecular weight of acrylic resin, the amount of silane modifier or fluorine-containing modifier has little effect on the hydrophobic properties of the prepared anti-corrosion coating.

[0187] The impedance results of the coatings prepared in Comparative Examples 16-30 immersed in 3.5 wt % NaCl solution for 1 day are shown in Table 8.

[0188] Table 8

[0189] Sample No. <![CDATA[Rs(Ω·cm 2 )]]> <![CDATA[C(Ω -1 ·cm -2 ·sn)]]> <![CDATA[Rp(Ω·cm 2 )]]> Comparative Example 16 <![CDATA[1.39×10 4 ]]> <![CDATA[4.19×10 -9 ]]> <![CDATA[3.64×10 6 ]]> Comparative Example 17 <![CDATA[1.45×10 4 ]]> <![CDATA[6.59×10 -9 ]]> <![CDATA[2.82×10 6 ]]> Comparative Example 18 <![CDATA[1.24×10 4 ]]> <![CDATA[4.38×10 -9 ]]> <![CDATA[3.46×10 6 ]]> Comparative Example 19 <![CDATA[1.71×10 4 ]]> <![CDATA[7.19×10 -9 ]]> <![CDATA[2.58×10 6 ]]> Comparative Example 20 <![CDATA[1.79×10 4 ]]> <![CDATA[7.63×10 -9 ]]> <![CDATA[2.34×10 6 ]]> Comparative Example 21 <![CDATA[1.63×10 4 ]]> <![CDATA[1.01×10 -9 ]]> <![CDATA[5.63×10 6 ]]> Comparative Example 22 <![CDATA[1.26×10 4 ]]> <![CDATA[8.13×10 -9 ]]> <![CDATA[2.18×10 6 <!-- 14 -->]]> Comparative Example 23 <![CDATA[1.96×10 4 ]]> <![CDATA[8.53×10 -9 ]]> <![CDATA[1.83×10 6 ]]> Comparative Example 24 <![CDATA[1.52×10 4 ]]> <![CDATA[9.87×10 -10 ]]> <![CDATA[5.84×10 6 ]]> Comparative Example 25 <![CDATA[1.31×10 4 ]]> <![CDATA[1.45×10 -9 ]]> <![CDATA[4.64×10 6 ]]> Comparative Example 26 <![CDATA[1.89×10 4 ]]> <![CDATA[1.05×10 -9 ]]> <![CDATA[5.21×10 6 ]]> Comparative Example 27 <![CDATA[1.15×10 4 ]]> <![CDATA[6.38×10 -9 ]]> <![CDATA[2.94×10 6 ]]> Comparative Example 28 <![CDATA[1.46×10 4 ]]> <![CDATA[5.73×10 -9 ]]> <![CDATA[3.12×10 6 ]]> Comparative Example 29 <![CDATA[1.85×10 4 ]]> <![CDATA[7.32×10 -9 ]]> <![CDATA[3.14×10 6 ]]> Comparative Example 30 <![CDATA[1.67×10 4 ]]> <![CDATA[8.14×10 -9 ]]> <![CDATA[2.33×10 6 ]]>

[0190] The impedance results of the coatings prepared in Comparative Examples 16-30 immersed in 3.5 wt % NaCl solution for 3 days are shown in Table 9.

[0191] Table 9

[0192] Sample No. <![CDATA[Rs(Ω·cm 2 )]]> <![CDATA[C(Ω -1 ·cm -2 ·sn)]]> <![CDATA[Rp(Ω·cm 2 )]]> Comparative Example 16 <![CDATA[1.31×10 4 ]]> <![CDATA[4.83×10 -8 ]]> <![CDATA[7.52×10 5 ]]> Comparative Example 17 <![CDATA[1.25×10 4 ]]> <![CDATA[6.73×10 -8 ]]> <![CDATA[6.51×10 5 ]]> Comparative Example 18 <![CDATA[1.64×10 4 ]]> <![CDATA[4.96×10 -8 ]]> <![CDATA[7.28×10 5 ]]> Comparative Example 19 <![CDATA[1.81×10 4 ]]> <![CDATA[7.34×10 -8 ]]> <![CDATA[6.23×10 5 ]]> Comparative Example 20 <![CDATA[1.59×10 4 ]]> <![CDATA[7.84×10 -8 ]]> <![CDATA[6.05×10 5 ]]> Comparative Example 21 <![CDATA[1.23×10 4 ]]> <![CDATA[2.46×10 -8 ]]> <![CDATA[8.75×10 5 ]]> Comparative Example 22 <![CDATA[1.46×10 4 ]]> <![CDATA[8.47×10 -8 ]]> <![CDATA[5.97×10 5 ]]> Comparative Example 23 <![CDATA[1.66×10 4 ]]> <![CDATA[8.96×10- 8 ]]> <![CDATA[5.73×10 5 ]]> Comparative Example 24 <![CDATA[1.42×10 4 ]]> <![CDATA[2.17×10 -8 ]]> <![CDATA[8.78×10 5 ]]> Comparative Example 25 <![CDATA[1.61×10 4 ]]> <![CDATA[3.45×10 -8 ]]> <![CDATA[8.32×10 5 ]]> Comparative Example 26 <![CDATA[1.19×10 4 ]]> <![CDATA[2.64×10 -8 ]]> <![CDATA[8.73×10 5 ]]> Comparative Example 27 <![CDATA[1.05×10 4 ]]> <![CDATA[6.54×10 -8 ]]> <![CDATA[6.62×10 5 ]]> Comparative Example 28 <![CDATA[1.02×10 4 ]]> <![CDATA[7.12×10 -8 ]]> <![CDATA[6.88×10 5 ]]> Comparative Example 29 <![CDATA[1.62×10 4 ]]> <![CDATA[9.38×10 -8 ]]> <![CDATA[7.92×10 5 ]]> Comparative Example 30 <![CDATA[1.59×10 4 ]]> <![CDATA[9.16×10 -8 ]]> <![CDATA[7.18×10 5 ]]>

[0193] The impedance results of the coatings prepared in Comparative Examples 16-30 when immersed in a 3.5 wt % NaCl solution for 7 days are shown in Table 10.

[0194] Table 10

[0195] Sample No. <![CDATA[Rs(Ω·cm 2 )]]> <![CDATA[C(Ω -1 ·cm -2 ·sn)]]> <![CDATA[Rp(Ω·cm 2 )]]> Comparative Example 16 <![CDATA[1.24×10 4 ]]> <![CDATA[7.46×10 -7 ]]> <![CDATA[5.05×10 5 ]]> Comparative Example 17 <![CDATA[1.17×10 4 ]]> <![CDATA[9.86×10 -7 ]]> <![CDATA[3.63×10 5 ]]> Comparative Example 18 <![CDATA[1.23×10 4 ]]> <![CDATA[7.96×10 -7 ]]> <![CDATA[4.95×10 5 ]]> Comparative Example 19 <![CDATA[1.32×10 4 ]]> <![CDATA[9.36×10 -7 ]]> <![CDATA[2.89×10 5 ]]> Comparative Example 20 <![CDATA[1.27×10 4 ]]> <![CDATA[9.84×10 -7 ]]> <![CDATA[2.63×10 5 ]]> Comparative Example 21 <![CDATA[1.15×10 4 ]]> <![CDATA[5.56×10 -7 ]]> <![CDATA[5.51×10 5 ]]> Comparative Example 22 <![CDATA[1.63×10 4 ]]> <![CDATA[1.07×10 -7 ]]> <![CDATA[2.17×10 5 ]]> Comparative Example 23 <![CDATA[1.59×10 4 ]]> <![CDATA[1.26×10 -7 ]]> <![CDATA[1.24×10 5 ]]> Comparative Example 24 <![CDATA[1.29×10 4 ]]> <![CDATA[5.46×10 -7 ]]> <![CDATA[5.53×10 5 ]]> Comparative Example 25 <![CDATA[1.38×10 4 ]]> <![CDATA[6.35×10 -7 ]]> <![CDATA[5.32×10 5 <!-- 15 -->]]> Comparative Example 26 <![CDATA[1.72×10 4 ]]> <![CDATA[5.64×10 -7 ]]> <![CDATA[5.45×10 5 ]]> Comparative Example 27 <![CDATA[1.56×10 4 ]]> <![CDATA[9.54×10 -7 ]]> <![CDATA[3.89×10 5 ]]> Comparative Example 28 <![CDATA[1.23×10 4 ]]> <![CDATA[8.62×10 -7 ]]> <![CDATA[2.88×10 5 ]]> Comparative Example 29 <![CDATA[1.38×10 4 ]]> <![CDATA[8.15×10 -7 ]]> <![CDATA[6.14×10 5 ]]> Comparative Example 30 <![CDATA[1.25×10 4 ]]> <![CDATA[9.20×10 -7 ]]> <![CDATA[5.97×10 5 ]]>

[0196] It can be seen from Tables 8-10 that when the molecular weight of the acrylic resin is larger (Comparative Example 16), the impedance radius of the prepared anti-corrosion coating is reduced by 1-2 orders of magnitude compared with Example 2. This may be because there are more gaps and microcracks between the large molecular weight acrylic resins, which increases the probability of corrosive substances contacting the substrate, thereby reducing the impedance radius of the coating.

[0197] By adjusting the components and ratios of the silane modifier and the fluorine-containing modifier (Comparative Examples 17-28), the inventors found that the impedance radius of the prepared anti-corrosion coating was reduced by 1-2 orders of magnitude compared with Example 2. This may be due to the different abilities of different silane modifiers and fluorine-containing modifiers to modify silica. Different components and ratios have different effects on modified silica. Adding a modifier may change the effect of modified silica, thereby significantly reducing the corrosion resistance.

[0198] Based on the modification of nano-silicon dioxide in Example 2, the inventors also adjusted the acrylic resin content, kaolin content and particle size, and found that the impedance radius of the prepared anti-corrosion coating was 2-4 orders of magnitude lower than that in Example 2, proving that the anti-corrosion performance was significantly reduced.

[0199] The inventor tested the corrosion of the prepared hydrophobic anti-corrosion coating in a simulated seawater environment to evaluate its corrosion resistance. The bare Q235 steel electrode sheet, the coating prepared in Example 1-6 and Comparative Example 1-30 were immersed in 50ml 3.5wt% NaCl and subjected to accelerated corrosion test at room temperature and atmospheric pressure, and the changes in surface morphology were recorded. The inventor found that at the beginning of 1 day of immersion, the surface of the bare electrode changed more obviously and a passivation film appeared, and it can be seen that the coatings of the embodiment and the comparative example have certain corrosion resistance to the substrate. However, after 1 week of immersion, blisters appeared on the edge of Comparative Example 1-15, cracks and rust spots appeared on the exposed part, and as the immersion time increased, the rust stains gradually spread to the center, and even after 2 weeks, the coating of Comparative Example 1-15 peeled off from the substrate, which means that the substrate lost the protective layer and produced yellow porous Fe2O3 corrosion products. After 2 weeks of immersion, slight blisters appeared on the edges of Example 1 and Comparative Examples 16-30. After 1 month of immersion, cracks and rust appeared on the exposed parts of Example 1 and Comparative Examples 16-30, and some of them fell off. However, the coating samples prepared by Example 2-6 were still very stable after immersion for 1 month, without obvious rust or falling off. This phenomenon is consistent with the electrochemical test results, which is attributed to the fact that after modification, nano-silicon dioxide synergizes with kaolin of a specific particle size and can be well dispersed in acrylic resin of a specific molecular weight. The synergistic effect of the three can fill the gaps on the surface of the coating, thereby blocking more corrosive media outside the coating surface. These characteristics improve the barrier and anti-corrosion properties of the coating.

[0200] The present invention regulates the dosage of kaolin and acrylic resin and the particle size of kaolin on the basis of modifying nano-silicon dioxide. It is found that the prepared coating has a certain anti-corrosion effect, but the impedance radius is reduced by 2-3 orders of magnitude compared with Example 2, proving that the anti-corrosion performance is deteriorated.

[0201] In summary, the present invention uses kaolin and acrylic resin to prepare the film. Kaolin with a specific particle size can reduce the porosity of the film as much as possible, and then the pores are further filled by adding modified nano-silica, so that the prepared coating has a better hydrophobic and anti-corrosion effect.

[0202] The above is a preferred embodiment of the present invention. For ordinary technicians in this technical field, without departing from the principles of the present invention, making several improvements and modifications should also be regarded as within the protection scope of the present invention.

Claims

1. A method for preparing a hydrophobic anticorrosive coating, characterized in that: include: Step 1: Preparation of nano-silicon dioxide; Step 2: adding kaolin powder, acrylic resin and nano-silica to ethyl acetate, performing ultrasonic dispersion and magnetic stirring at room temperature to obtain a pre-cured mixed solution; the mass ratio of kaolin powder, acrylic resin and nano-silica is 1:0.66:0.05; Step 3: Apply the pre-cured mixed liquid dropwise on the substrate and cure it to obtain a hydrophobic anti-corrosion coating.

2. The method for preparing the hydrophobic anticorrosive coating according to claim 1, characterized in that: In the step 2, the particle size of the kaolin powder is 1-10 μm.

3. The method for preparing the hydrophobic anticorrosive coating according to claim 2, characterized in that: The kaolin powder is a mixture of particle sizes of 1-4µm and 5-8µm in a mass ratio of 1:2.5; the molecular weight of the acrylic resin is 10000-50000.

4. The method for preparing the hydrophobic anticorrosive coating according to claim 3, characterized in that: The mass ratio of the ethyl acetate volume to the acrylic resin is 5:

1.

5. The method for preparing the hydrophobic anticorrosive coating according to claim 4, characterized in that: In the step 2, ultrasonic dispersion is performed for 30-60 minutes and magnetic stirring is performed for 1-4 hours.

6. The method for preparing the hydrophobic anticorrosive coating according to claim 5, characterized in that: In step 2, the substrate is a Q235 steel electrode sheet or a glass sheet; the amount of the pre-cured mixed solution applied is 0.5-2 mL / cm 2 .

7. The method for preparing the hydrophobic anticorrosive coating according to claim 6, characterized in that: In the step 2, curing is performed at room temperature for 12-24 hours.

8. The method for preparing a hydrophobic anticorrosive coating according to claim 1, characterized in that: The preparation method of the nano-silica is as follows: an anhydrous ethanol solution and ammonia water with a volume ratio of 1:1 are dispersed in a beaker; the solution is placed in a magnetic stirring for 0.5 h; then 2 ml of tetraethoxysilane (TEOS) is added dropwise into the mixed solution which is continuously stirred for 4 h; then the mixture is stirred at 5000 r min -1 Centrifuge for 30 minutes, remove the supernatant, filter the solid, and wash it with ethanol 2-5 times to obtain silica nanoparticles.

9. The method for preparing a hydrophobic anticorrosive coating according to claim 1, characterized in that: The preparation method of the nano silicon dioxide is as follows: ① Mixing anhydrous ethanol solution and aqueous ammonia, and then stirring the mixed solution to mix evenly to obtain a mixed solution; The volume ratio of the ethanol solution to the ammonia water is 1:1; the volume fraction of ethanol in the ethanol solution is 90%, and the mass fraction of NH3·H2O in the ammonia water is 25% to 28%; ② Add the silane modifier to the above mixed solution and stir evenly; The silane modifier is dimethyldiethoxysilane, vinyltrimethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 1:1.5:2; the volume ratio of the mass of the silane modifier to the mixed solution in ① is: 0.5-0.8g:100mL; ③ Under stirring conditions, add tetraethoxysilane dropwise into the mixed solution in ②, and continue stirring for 2-6 hours; the volume ratio of the tetraethoxysilane to the mixed solution in ① is 1:50-100; ④ Then add the fluorine-containing modifier and stir evenly; the fluorine-containing modifier is hexafluorobutyl methacrylate and 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane in a mass ratio of 1:0.8; the mass ratio of the fluorine-containing modifier to the silane modifier is 1:0.4-0.6; ⑤ Then centrifuge to obtain a solid product, wash the solid product with anhydrous ethanol for 2 to 5 times, dry it, grind it and sieve it to obtain nano silicon dioxide.

10. An anti-corrosion coating prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Superhydrophobic acrylic resin paint

    CN102417773A

  • Super-hydrophobic anti-pollution flashover coating capable of being used for electrified construction, and preparation method thereof

    CN111269628A

  • Multifunctional superhydrophobic diatomaceous earth for chemical adhesion and color change

    CN104321279A

  • Modified nano-composite super-hydrophobic coating and preparation method thereof

    CN110028862A

  • Compression-resistant and wear-resistant hydrophobic anticorrosive paint as well as preparation method and application thereof

    CN116410638A